Deciphering the Bacillus amyloliquefaciens B9601-Y2 as a Potential Antagonist of Tobacco Leaf Mildew Pathogen During Flue-Curing - Pan, Zuxian; Munir, Shahzad; Li, Yongmei; He, Pengbo; He, Pengfei; Wu, Yixin; Xie, Yan; Fu, Zongwei; Cai, Yongzhan; He, Yueqiu (Frontiers in Microbiology, 2021)
Tobacco leaf mildew caused by Rhizopus oryzae (Mucorales, Zygomycota) is an important and devastating post-harvest disease during flue-cured tobacco period, and also is known to cause diseases of fruits and vegetables. In this study, assessment of several candidate biological control agents were first tested in vitro to determine their antifungal activities and potential strains were further applied to tobacco leaves to prevent pathogen colonization during tobacco-curing process. In vitro screening of 36 bacteria and one fungus isolates were performed for their antifungal activities against R. oryzae using dual culture method. Potential five isolates viz. Bacillus amyloliquefaciens B9601-Y2 (Y2), B. amyloliquefaciens YN201728 (YN28), Pseudomonas sp. (Pb), and B. amyloliquefaciens YN201732 (YN32) and T. harzianum B (Th-B) from total screened isolates have shown remarkable results of controlling the mycelial growth of R. oryzae. Finally, out of these five isolates B. amyloliquefaciens B9601-Y2 potentially reduced mycelial growth of fungal pathogen with great inhibitory effect. In order to get better understanding of biocontrol effect of B9601-Y2 in flue-curing barn, various suspension density tests with two application methods involving spraying and soaking were resulted. Two application methods of B. amyloliquefaciens B9601-Y2 had 98.60% and 98.15% control effects, respectively. In curing barn, the incidence in the treatment group was significantly reduced and tobacco leaves did not get mildew. Altogether, the study demonstrated that candidate bacterial strain B. amyloliquefaciens B9601-Y2 is a potential antagonist for the management of tobacco leaf mildew during flue-curing.